Stimuliert der BioRegio-Wettbewerb die Bildung von Biotechnologieclustern in Deutschland? - Dirk Engel; Oliver Heneric (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
Regions with biotechnology-specific knowledge seem to have best chances to attract potential entrepreneurs to establish a biotechnology-firm. Furthermore, regional oriented technology policy is supposed to stimulate the creation process of biotechnology clusters, too. The BioRegio contest (BRC) is the most prominent example for this kind of policy support. The analysis tries to test both hypotheses empirically. Our estimation results are in accordance with expectations and empirical evidence for the US: Scientists at public research institutes are key players for the commercialization of radical biotechnology discoveries in the region of their place. BRC participating regions have best conditions to attract biotech companies on average. Further, exclusive financial support of BRC winning regions does not contribute significantly to cluster biotechnology industry stronger than in non-winning regions.
Keywords: R30; C21; O30; R58; 330; Biotechnology; start-ups; economic geography; technology policy; count data model; Biotechnische Industrie; Biotechnische Forschung; Standortfaktor; Räumliche Verteilung; Deutschland